2013
DOI: 10.1503/cmaj.121802
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of primary care practices associated with high quality of care

Abstract: A health care system is only as strong as its primary care sector, 1 which provides "entry into the system for all new needs and problems, provides person-focused (not disease-oriented) care over time, provides care for all but very uncommon or unusual conditions …" 2 Patient enrolment, team-based care, information technology, and funding and remuneration schemes that foster comprehensiveness and collaboration are key characteristics of effective primary care systems.3 None can be singled out as the most deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 37 publications
1
60
0
Order By: Relevance
“…In addition, the results of our observational study provide evidence on the construct validity of our short French version because the TCI score was associated with the overall technical quality of PC score (Beaulieu et al 2013). Having access to a valid and reliable measure of team processes in both French and English is an asset for Canadian health services researchers and decision-makers.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…In addition, the results of our observational study provide evidence on the construct validity of our short French version because the TCI score was associated with the overall technical quality of PC score (Beaulieu et al 2013). Having access to a valid and reliable measure of team processes in both French and English is an asset for Canadian health services researchers and decision-makers.…”
Section: Discussionmentioning
confidence: 70%
“…A shortened 14-question version has been proposed by a Finnish team (Kivimäki and Elovainio 1999), but that version is not based on a robust methodology and has yet to be associated with health outcomes. However, the authors of the original TCI have validated a shorter 19-item version (M. West, personal communication, October 1, 2008) that we translated into French and used in a study of the association between organizational characteristics of PC practices and quality of care (Beaulieu et al 2013). In that study, we demonstrated that this short version of the TCI was among the predictors of better quality of care.…”
Section: Résumémentioning
confidence: 86%
See 2 more Smart Citations
“…Other studies investigating relationships between diabetes/ chronic disease care and practice characteristics (including EHR, 33 Medicaid percentage, 34 community health centers, [35][36][37] and practice size 38,39 ) have reported mixed results. Interestingly, we find that rural and smaller practices, which often do not have as many connections to resources as urban practices, showed significantly greater improvement in both the CQI-and RAP-facilitated arms, while urban practices, usually with more available resources, saw more improvement in the self-directed arm.…”
Section: Discussionmentioning
confidence: 99%